Excellent supercapacitive performance of graphene quantum dots derived from a bio-waste marigold flower (Tagetes erecta) - Gupta G.K.; Sagar P.; Srivastava M.; Singh A.K.; Singh J.; Srivastava S.K.; Srivastava A. (My University, 2025)
Marigold flower (MG; Tagetes erecta) derived Graphene quantum dots (GQDs) have been successfully reported for the fabrication of supercapacitor electrodes in charge storage devices. The GQDs have been synthesized through a hydrothermal route using biomass viz. Waste material (MG) without adding any hazardous chemicals. The successful formation of GQDs as elaborated has been confirmed by various analytical characterization techniques. The as-synthesized GQDs have been electrodeposited on the Ni foil (working electrode) with the help of PVDF (binder) and subsequently, cyclic voltammetry (CV) has been conducted to access specific capacitance, energy density, and other parameters. Moreover, the galvanometric charge/discharge (GCD) technique has been employed due to its accuracy and reliability. Maximum areal specific capacitance has been found as 1.6008 F/cm2 with the current density of 2.0 A/g even after loading a little amount of material on the electrode. The high magnitude of columbic efficiency (160.08), energy density (17.78 Wh/kg), and specific capacitance of 200 F/g at current density 2.0 A/g within a voltage range of −0.55 V to +0.25 V in 2 M KOH electrolyte solution indicate a good electrocapacitive performance of the as-synthesized material. Moreover, the as-synthesized GQDs have shown excellent capacitive retention after 1000th cycles which clearly embarks its sustainable electrocapacitive nature and henceforth offers outstanding potential for the applications in energy storage devices like supercapacitors. © 2021